Control in the Face of Uncertainty: Is Job Insecurity a Challenge to the Mental Health Benefits of Control Beliefs?. (December 2014) - Glavin, Paul; Schieman, Scott
The mental health benefits of the sense of personal control are well documented, but do these benefits persist in social contexts of powerlessness and uncertainty? Drawing from two national panel surveys of American and Canadian workers, we examine whether the association between perceived control and reduced distress is undermined by the uncertainty of threatened employment. While we find evidence that higher levels of perceived control are associated with reduced distress, the association is curvilinear among insecure workers, such that subsequent increases in control produce diminishing reductions in distress for workers reporting the threat of job loss. This curvilinear pattern is particularly prominent among American insecure workers, with higher than moderate levels of control associated with more rather than less distress for this group. We draw from Mirowsky and Ross's "instrumental realism" model to interpret these patterns and suggest that high control beliefs may be less beneficial for mental health in uncertain role contexts.